Pengetahuan Gizi dan Persepsi terhadap Perilaku Konsumsi Makanan Pemicu Kanker - Indah Ditasari; Ditia Fitri Arinda (Sarana Ilmu Indonesia (salnesia), 2022)
One way to avoid the problem of degenarative disease or non-communicable disease is to have healthy eating behaviors. The goal of this study is to see if there is a link between nutrition education and perceptions of cancer-causing food consumption in Sriwijaya University students who are subjected to confounding variables. The distribution of a google form to 238 students was randomized using random sampling in this study. The perception variable 0,021 (p-value 0,05) was shown to be the most important factor in Sriwijaya University students consumption of cancer-causing foods. after being influenced by things such as friends knowledge and influence It is critical for prevention initiatives such as enhancing students nutritional understanding so that their knowledge and perceptions both improve.